Deformation Behavior of Coarse-Grained Soil as an Embankment Filler under Cyclic Loading - Zhong-Ming He; Da Xiang; Ya-Xin Liu; Qian-Feng Gao; Han-Bing Bian (Advances in Civil Engineering)
This study aims to examine the deformation behavior and internal mechanism of coarse-grained soil as an embankment filler under cyclic loading. Numerical dynamic triaxial tests were performed on coarse-grained soil using the discrete element software PFC3D. The numerical model was verified by comparing the numerical results with the experimental data. Afterward, the changes in the porosity, force chain, and particle movement of coarse-grained soil samples were analyzed, and the mesoscopic deformation behavior of coarse-grained soil under cyclic loading was investigated. The research results show that with the increase of the deviatoric stress amplitude, moisture content, and loading frequency, the deformation of the soil increases and the ability to resist deformation decreases at the same loading cycles. Due to the inhomogeneous distribution of particles with different sizes, the velocity and displacement of the sample vary in different directions, exhibiting mesoscopic anisotropy. The contact force is relatively even in the downward direction while dispersed near the edge of the sample. This means that the particles at the bottom are less affected by loads and the internal evolution of soil samples conforms to its macroscopic deformation behavior during cyclic loading.